A PARALLEL PIPELINED PACKET SWITCH ARCHITECTURE FOR MESH-CONNECTED MULTIPROCESSORS WITH INDEPENDENTLY ROUTED FLITS - Jamil Al-Azzeh; Mohammed Agmal; Igor Zotov (Jordanian Journal of Computers and Information Technology, 2019)
In this paper, a packet switch architecture for mesh-connected multiprocessors based on the use of a set of in-put FIFO buffers and an output register matrix controlled by a novel distributed timing-based scheduling scheme is proposed. Simple static routing is assumed, with each packet split into a set of independently routed w-bit-wide flits. The device achieves at least 78% throughput for uniformly distributed traffic and an asymptot-ic higher bound of 100%. In contrast to the state-of-the-art VOQ-based switch architectures, the proposed switch is shown to reach its maximum throughput with no internal speedup required and has an order of mag-nitude lower hardware complexity. Compared to existing buffered crossbar non-VOQ switches with typical flit scheduling mechanisms, the proposed device demonstrates slightly higher throughput and substantially short-er delays in some practically important cases.